2022
DOI: 10.32604/cmc.2022.026515
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Computing-Based Mammographic Image Classification on an Internet of Medical

Abstract: Recently, the Internet of Medical Things (IoMT) has become a research hotspot due to its various applicability in medical field. However, the data analysis and management in IoMT remain challenging owing to the existence of a massive number of devices linked to the server environment, generating a massive quantity of healthcare data. In such cases, cognitive computing can be employed that uses many intelligent technologies-machine learning (ML), deep learning (DL), artificial intelligence (AI), natural languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Given this, it is deduced that ML is a reliable network for detecting cancer that was not detected by the initial reader [17]. It was also observed that ML provides support for radiologists, according to several articles [1][2][3], [6], [7], [11], [17], [18], [20][21][22][23], [29], so it is deduced to be the main advantage since it is the most mentioned in the reviewed articles. ML would help doctors build a comprehensive and personalized view of each patient and assist in making judgments and decisions [11].…”
Section: Advantages Of Machine Learning In Breast Cancer Detectionmentioning
confidence: 95%
See 3 more Smart Citations
“…Given this, it is deduced that ML is a reliable network for detecting cancer that was not detected by the initial reader [17]. It was also observed that ML provides support for radiologists, according to several articles [1][2][3], [6], [7], [11], [17], [18], [20][21][22][23], [29], so it is deduced to be the main advantage since it is the most mentioned in the reviewed articles. ML would help doctors build a comprehensive and personalized view of each patient and assist in making judgments and decisions [11].…”
Section: Advantages Of Machine Learning In Breast Cancer Detectionmentioning
confidence: 95%
“…Finally, the number of articles was reduced to 26, which will be used to develop the systematic literature review. From the different databases, eight articles published during the year 2023 were identified [1], [3], [4], [6], [11], [13], [14], along with eight articles from the year 2022 [2], [5], [7][8][9][10], [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], all of which met the filters established in the methodology, and that is why they were selected. The will above aids in conducting the review with data from up-to-date research grounded in knowledge from subsequent years.…”
Section: Jimenez Ayalamentioning
confidence: 99%
See 2 more Smart Citations
“…28 This current review extracted and organized the data in tabular form and summarized the use of MG in the diagnosis of breast cancer (Table 1). 2,4,5,7,9,24,2979…”
Section: Introductionmentioning
confidence: 99%